Gender differences in the returns to education in Mexico - Caamal Olvera, Cinthya Guadalupe (World Business Institute, 2013)
ABSTRACT The aim of this paper is to examine the trend over time of the rewards to education granted by the Mexican labor market accounting for gender differences. The paper provides robust estimates of the returns to education across the conditional wage distribution using quantile regression methodology. The estimated coefficients reveal a robust declining trend stronger for males than for females. The estimates of the returns to education are larger for females than for males, which may be explained by women’s acquisition of more schooling than males and their increasing participation in the labor market. Yet even as returns to education increase for women, the jobs they hold continue to pay lower wages relative to men.